European Municipalities Engaging in Climate Change Mitigation and Adaptation Networks: Examining the Case of the Covenant of Mayors. - Haupt, Wolfgang (Springer, 2018)
Over the past years a considerable number of towns and cities joined together in transnational networks, which aim to take action on climate change. With regards to European municipalities this development was supported by two major trends: First, an increased willingness of cities worldwide to tackle major global issues jointly. Secondly, a realignment of spatial policies towards cities and urban areas on the EU level. This chapter focuses on one of the more recent networks: The European mainstream climate initiative Covenant of Mayors. The signatories of this initiative explicitly seek the collaboration with other communities in order to share knowledge and experience, and thus improve their own climate change mitigation and adaptation measures in order to enhance its climate resilience. Implementing a local action plan is often dependent on external funding, wherefore particularly communities from the crisis-ridden Southern European countries struggle in its realization. To facilitate the signatories’ work and to respond to these difficulties, their efforts are complemented by various decision-making support tools and through conceding access to European funding programs.
Keywords: Stadtentwicklungspolitik; Bürgermeister; Interkommunale Zusammenarbeit; Internationale Zusammenarbeit; Städtenetz; Klimawandel; Klimaanpassung; Umweltvorsorge; Nachhaltige Entwicklung; Finanzierung